2021
DOI: 10.1038/s41598-021-91135-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of high-efficiency particulate air filtration on mortality among multiple myeloma patients receiving autologous stem cell transplantation

Abstract: Autologous stem cell transplantation (ASCT) continues to be the standard treatment for transplant-eligible multiple myeloma (MM) patients. A portion of MM patients received ASCT in an isolation room with high-efficiency particulate air (HEPA) filtration. The effectiveness of the HEPA filtration on reducing treatment-related mortality (TRM) is controversial. We enrolled patients with newly diagnosed MM in Taiwan between 2000 and 2017. The primary endpoint of the study was TRM, which was defined as death within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…A similar experience has been published by Kumar et al, who demonstrated acceptable infection rates and survival in 40 patients who underwent allogeneic HSCT in non-HEPA-filtered rooms without positive pressure 14 . Tsai et al demonstrated that the 100-day mortality in adult patients with multiple myeloma did not differ if the room used was without a HEPA filter 15 .…”
Section: Discussionmentioning
confidence: 99%
“…A similar experience has been published by Kumar et al, who demonstrated acceptable infection rates and survival in 40 patients who underwent allogeneic HSCT in non-HEPA-filtered rooms without positive pressure 14 . Tsai et al demonstrated that the 100-day mortality in adult patients with multiple myeloma did not differ if the room used was without a HEPA filter 15 .…”
Section: Discussionmentioning
confidence: 99%
“…No recommendation can be made for routinely placing a recipient of autologous HSCT or solid organ transplant in a protected environment [ 38 ]. When assessing the effectiveness of the HEPA filtration on reducing treatment-related mortality in multiple myeloma patients receiving autologous stem cell transplantation, Tsai et al found it didn’t affect 100-day mortality [ 64 ].…”
Section: Infection Prevention and Control Measuresmentioning
confidence: 99%